High Abdominal Perfusion Pressure Using Umbilical Cord Flap in the Management of Gastroschisis - Arafa, Mohamed Ahmed; Elshimy, Khalid Mohamed; Shehata, Mohamed Ali; Elbatarny, Akram; Almetaher, Hisham Almohamady; Seleim, Hamed Mahmoud (Frontiers in Pediatrics, 2021)
Abstract Background:- Gastroschisis management remains a controversy, Most surgeons prefer reduction and fascial closure. Others advised staged reduction to avoid a sudden rise in intra-abdominal pressure. The aim of this study to use the umbilical cord as a flap for tension-free repair of gastroschisis. Methods:- A prospective study of neonates with gastroschisis repaired between January 2018 to October 2020 in Tanta university hospital. We used the umbilical cord as a flap after the evacuation of all its blood vessels and suturing the edges of the cord with the skin edges of the defect. They were guided by monitoring Abdominal Perfusion Pressure (APP), Peak Inspiratory Pressure ( PIP ), Central Venous Pressure ( CVP ) and urine output during and 24, 48 hrs. postoperatively. Results: - In 20 cases had gastroschisis with a median age of 24 h, We applied umbilical cord flap in all cases then purse string ( Prolene Zero ) with daily tightening till complete closure in 7 cases, secondary suturing after 10 days in 4 cases, and leaving skin creeping until complete closure in 9 cases during the trials of closure the range of APP was 49-52 mmHg. The range of IAP (IVP) was 15-20 cm.H2O (11-15 mmHg), the range of PIP was 22-25 cm.H2O, the range of CVP was 13-15 cm.H2O and the range of urine output was 1-1.5 ml/kg/hr. Conclusion:- Umbilical cord flap is an easy, feasible, and cheap method for tension-free closure of gastroschisis with limiting the PIP ≤ 24 mm.Hg, IAP ≤ 20 cm.H2o (15 mmHg), APP > 50 mm.Hg and CVP ≤ 15cm.H2o.